Pengembangan Model Analisis Faktor Resistensi untuk Rekomendasi Peningkatan Niat Bermain Game Digital Menggunakan PLS-SEM - Chamdana Taqie Samboro; Mudjahidin Mudjahidin (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
There is a lot of research on the intention to play games, but rarely does it look at the barriers that make someone reluctant and resistant to playing games. This study aims to: develop barrier factors (interpersonal, intrapersonal and structural factors) by considering health factors that cause someone to refuse to play games using a sample of 230 respondents in Malang, Indonesia, who have stopped playing games for at least the last 3 months, using a Google form. The analysis in this study used PLS-SEM to conduct an outer test on the questionnaire and an inner test on the path model and test the hypothesis. The findings proved that: all barriers, including interpersonal, intrapersonal, structural, and health barriers, trigger significant resistance and then reduce interest in playing digital games. These findings provide information and recommendations for game developers to design game designs and features that are more inclusive, balanced, and support the physical and mental health of users, in order to minimize resistance in playing digital games.